Musculoskeletal complaints in military recruits during their basic training. Issue 4 (29th October 2020) - Keijsers, Noel L W; ter Stal, M; Jonkergouw, N; Helmhout, P H
Abstract : Introduction: Overuse injuries often start with a musculoskeletal complaint, which can progress over time to an injury. Little or no information is known about the development and severity of overuse injuries in military recruits. This study describes the musculoskeletal complaints in Dutch military recruits during their basic training and examines potential predictive factors for dropout due to injury. Methods: In this prospective cohort study, Dutch military recruits reported complaints of the lower body weekly using a Numeric Rating Scale (NRS) pain score chart during their basic training. Number, location and severity of complaints during each of the first 12 weeks of basic training were analysed. Results: Of the 930 recruits, 61% reported an NRS pain score of 3 or higher and 34% reported an NRS pain score of 5 or higher at least once. Complaints were mostly reported in the foot and ankle region and least reported in the upper leg region. Injury dropouts (11%) showed significantly higher proportions of complaints and higher maximal pain scores throughout most weeks of basic training. The maximal NRS pain score of the first two weeks was the strongest predictor of dropping out due to injury. Conclusions: Recruits who drop out due to injury report more severe complaints throughout basic training. Focusing on musculoskeletal complaints in the first phase of training seems helpful to identify recruits who are at risk of developing an injury.